Inheritance of primary grain morphology traits in oat - Cabral, Cândida Braga; Milach, Sandra Cristina Kothe; Pacheco, Marcelo Teixeira; Crancio, Leonardo Araripe (Pesquisa Agropecuaria Brasileira, 2001)
The production of varieties with higher grain physical quality has acquired importance, especially with the globalization of the South American markets. In order to define the best strategies for the improvement of these traits, it is important to study their genetic basis, and until now, studies of this nature have not been conducted with Brazilian oat genotypes. This work was carried out with the objective of determining the inheritance and heritability of the area, length, width and perimeter of primary oat grains. Samples of 20 grains of a variable number of plants from the generations P1, P2, F1, F2 e F3 from five crosses were evaluated through analysis of digitalized images. From these data frequency distributions and variances were obtained and heritability values were estimated in broad sense and parent offspring, as well as the predominant gene effects. The results showed that there is variability in early generations for the grain traits evaluated and that additivity and dominance are the main gene effects acting. The presence of major genes was not detected in the expression of these traits, and continuous variation in the F2 indicates that low selection pressure has to be applied in early generations.